IMPACT OF INTRINSIC AEROBIC EXERCISE CAPACITY ON CARDIOVASCULAR OUTCOMES FOLLOWING VARIOUS FORMS OF CARDIOVASCULAR STRESS - Alsahly, Musaad Bedah (East Carolina University, 2020)
Cardiovascular diseases (CVD) remain the major leading cause of death in the western world. Therefore, several approaches to achieve cardioprotection against any cardiovascular insult have been explored and to date, the only practical and justifiable countermeasure capable of providing cardioprotection is regular sessions of endurance exercise. However, active exercise programs, while consistently beneficial, still generate a very diverse response, suggesting the potential for critical contribution from the genetic composition determining intrinsic aerobic exercise capacity. It has been estimated that up to 60-70% of the variation in exercise capacity is due to the genetic component. This heterogeneous response elaborates the importance of investigating the influence of intrinsic exercise capacity alone (independently from any other external factors such as exercise training) on the vascular, metabolic and myocyte adaptive responses following acute, chronic, or even to non-cardiovascular stress. Intrinsic capacity can be studied using high (HCR) and low (LCR) aerobic running capacity rat strains. The phenotypes differ by more than 5-fold in sedentary average running distance and time. The selection process used to develop these animals has generated a shift in metabolic and cardiovascular risk factors between the two strains. LCR rats have accumulated cardiovascular risk factors, such as a large gain in visceral adiposity, hypertension, dyslipidemia, impaired glucose tolerance, endothelial dysfunction, hyperglycemia, hypertriglyceridemia, insulin resistance and elevated plasma free fatty acids. LCR phenotype scored high on cardiovascular risk factors and the HCR score high for health factors. Therefore, we tested the hypothesis that LCR phenotype will greater alterations in vascular, metabolic, and cardiac adaptive responses to various forms of cardiovascular stress, including doxorubin-induced cardiotoxicity, and ischemia reperfusion injury in vivo and ex vivo. We found that phenotypic vascular reactivity differences presented in males but not females and females had higher responses to vasoconstriction (endothelin 1) and vasodilation agents (Ach) in both strains. Aged HCR and LCR animals treated with Doxorubicin did not differ in resting cardiac function. However, HCRs decreased ejection fraction (lost contractility) and increased heart rate (reflex tachycardia) 10 days after Dox, but LCRs did neither. Moreover, LCRs had significantly higher mitochondrial respiration after Dox while HCRs appeared to have been physiologically primed and therefore did not exhibit an adaptive compensatory response. With 30 min coronary artery ligation followed by 2 hr. reperfusion, there was no differences in infarct size between HCRs and LCRs, but males in both phenotypes showed larger infractions than females. However, with 15 min coronary artery ligation followed by 2 hr. reperfusion, HCRs showed smaller myocardial infarct size comparing to LCR counterparts. The sex differences were maintained in both strains with different time frames of coronary ligation. In acute ischemic reperfusion (IR) study, cardiac mitochondria from HCR were significantly higher in control conditions with each substrate tested. However, after IR insult, the cardiac mitochondrial respiratory rates were similar between phenotypes, as was infarct size. In these post IR fibroblast/myofibroblasts, LCRs showed significantly higher gene expression in collagen I, lower collagen III and higher collagen I/collagen III ratio. Furthermore, LCRs showed lower expression of extracellular matrix regulatory genes including MMP2, TIMP1, and SMAD5 compared to HCRs counterparts. BMPR2, Agtr1a, also were both decreased, and the anti-apoptotic gene, Bag3, was significantly higher in LCRs. Moreover, The Angiotensin receptor pathway is responsive only in post-ischemic LCR cardiac fibroblasts, and the BMP receptor pathway is responsive only in post-ischemic HCR cardiac fibroblasts.
Keywords: Exercise Tolerance; Cardiovascular System; Exercise